A Role for the Ste20-Like Kinase, SLK, in Cell Cycle Progression - O'Reilly, Paul G (University of Ottawa (Canada), 2010)
The Ste20-like kinase, SLK, is a serine/threonine kinase that has been shown to have a role in migration (Roovers et al., 2009; Storbeck et al., 2009; Wagner et al., 2002; Wagner et al., 2008) and cell cycle progression (Ellinger-Ziegelbauer et al., 2000). The latter of these two observations prompted us to investigate the functional role of SLK during G2/M. Consistent with the findings of Ellinger-Ziegelbauer et al., 2000, we observed an elevation in SLK activity when synchronized populations of murine fibroblasts enter the G2/M compartment of the cell cycle but report a 3-4 fold increase in activity in contrast to the modest 1.3 fold increase previously reported. The expression of a catalytically inactive truncation of SLK (SLK1-373K63R, termed KDeltaC) results in delayed G2 kinetics. This was evidenced by KDeltaC-expressing cultures that fail to down regulate cyclin A, to activate cdc2, and to undergo H3 phosphorylation at appropriate times. Supporting this observation, microinjection of a constitutively active truncation of SLK (SLK1-373, termed YDeltaC) resulted in ectopic mitotic spindle formation in fibroblasts and induced cell cycle re-entry in Xenopus oocytes. During the course of a yeast two hybrid screen we identified MARK3, a kinase that has links to G2 progression through Cdc25C phosphorylation (Ogg et al., 1994; Peng et al., 1998; Peng et al., 1997), as a SLK interacting protein. We show that SLK is capable of directly binding MARK3 and is capable of phosphorylating a central domain fragment of MARK3 in vitro but could not demonstrate a functional role for this phosphorylation event in vivo. Finally, we show that SLK phosphorylates the focal adhesion adaptor protein paxillin in vitro in its amino-terminal LD domain. In addition, we followed up on the previous observation that MARK3 interacts with paxillin (Migration Gateway, 2009) and show that this interaction is direct. We then present evidence that SLK, MARK3, and paxillin form a complex that is most evident during the G2/M compartment of the cell cycle. We propose that MARK3 is responsible for localizing SLK to paxillin during G2/M where it phosphorylates paxillin leading to a "loosening" of the cells which is required for cell rounding and division.
Keywords: Biology, Molecular.